In Kanker... Nutritional gardens for health and wealth - Sahu, Birbal; Markan, Suresh (Indian Horticulture, 2019)
Nutritional gardens were established in schools of Kanker district under the Farmer FIRST Programme to overcome the challenge of malnutrition in children.